2015
DOI: 10.1208/s12249-015-0448-0
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Method for Preparing Surface-Modified Fluocinolone Acetonide Loaded PLGA Nanoparticles for Ocular Use: In Vitro and In Vivo Evaluations

Abstract: ABSTRACT. Our objective was to prepare nanoparticulate system using a simple yet attractive innovated method as an ophthalmic delivery system for fluocinolone acetonide to improve its ocular bioavailability. Poly(lactic-co-glycolic acid) (PLGA) nanoparticles were prepared by adopting thin film hydration method using PLGA/poloxamer 407 in weight ratios of 1:5 and 1:10. PLGA was used in 75/25 and 50/50 copolymer molar ratio of DL-lactide/glycolide. Results revealed that using PLGA with lower glycolic acid monome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 48 publications
2
27
1
Order By: Relevance
“…The average particle size of the cubosomes nanoparticles as well as their size distribution (polydispersity index; PDI) were measured by a particle analyzer (Zetasizer Nano ZS, Malvern (Salama et al, 2016) was dispersed in acetonitrile and were vortexed for 10 min (Reax top, Heidolph, Germany). The drug content was then analyzed by LC-MS/MS method following the procedure reported below.…”
Section: Characterization Of the Etodolac-loaded Cubosomes Dispersionsmentioning
confidence: 99%
“…The average particle size of the cubosomes nanoparticles as well as their size distribution (polydispersity index; PDI) were measured by a particle analyzer (Zetasizer Nano ZS, Malvern (Salama et al, 2016) was dispersed in acetonitrile and were vortexed for 10 min (Reax top, Heidolph, Germany). The drug content was then analyzed by LC-MS/MS method following the procedure reported below.…”
Section: Characterization Of the Etodolac-loaded Cubosomes Dispersionsmentioning
confidence: 99%
“…For example, chitosan was used as a coating for PLGA NPs and showed a sustained delivery of forskalin and thus, a greater IOP lowering effect and duration compared to standard forskalin solution. Chitosan-coated PLGA NPs have also been used to deliver fluocinolone to the anterior segment of rabbit eyes [98]. Results showed that chitosan coating increased and sustained drug release by PLGA NPs.…”
Section: Combination Of Natural and Synthetic Polymersmentioning
confidence: 99%
“…The results concerning both the coating with NACCS compared to CS oligosaccharides or carboxymethyl CS [312], as well as the content of thiol groups [313], were the same ( Figure 22B). Salama et al used PLGA 50/50 or 75/25 in NP formulation of fluocinolone acetonide (FA), which is an anti-inflammatory corticosteroid drug used for the treatment of intermediate, posterior, and pan uveitis [314]. NPs were prepared by an innovative thin film hydration process using P407 in a mass ratio of PLGA/P407 1:5 and 1:10.…”
Section: Chitosan Coatingsmentioning
confidence: 99%